Three-Axes Attitude Control of Solar Sail Based on Shape Variation of Booms - Feng Zhang; Shengping Gong; Hexi Baoyin (Aerospace, 2021)
Actively controlling the attitude of the solar sail is necessary to adjust the solar radiation pressure force for trajectory transfer and orbit control. The special configuration of the solar sail makes it very important to develop a unique attitude control strategy that differs from traditional methods. An attitude control method, based on shape variation of booms, is proposed in this manuscript. Firstly, we derive the equations to calculate the solar radiation pressure force and torque of the deformed solar sail. Then, the factors affecting forces and torques are analyzed. Finally, PD control law is applied to realize the three-axis attitude control for the solar sail.